In Vitro Three‐Dimensional Liver Models for Nanomaterial DNA Damage Assessment. Issue 15 (15th January 2021) - Llewellyn, Samantha V.; Niemeijer, Marije; Nymark, Penny; Moné, Martijn J.; van de Water, Bob; Conway, Gillian E.; Jenkins, Gareth J. S.; Doak, Shareen H.
Abstract: Whilst the liver possesses the ability to repair and restore sections of damaged tissue following acute injury, prolonged exposure to engineered nanomaterials (ENM) may induce repetitive injury leading to chronic liver disease. Screening ENM cytotoxicity using 3D liver models has recently been performed, but a significant challenge has been the application of such in vitro models for evaluating ENM associated genotoxicity; a vital component of regulatory human health risk assessment. This review considers the benefits, limitations, and adaptations of specific in vitro approaches to assess DNA damage in the liver, whilst identifying critical advancements required to support a multitude of biochemical endpoints, focusing on nano(geno)toxicology (e.g., secondary genotoxicity, DNA damage, and repair following prolonged or repeated exposures). Abstract : A significant challenge facing engineered nanomaterial hazard assessment is the application of physiologically relevant in vitro models for evaluating genotoxicity. This review considers the benefits, limitations, and adaptations of 3D in vitro liver culture systems to assess DNA damage. Important advances that facilitate the evaluation of a range of genotoxicity endpoints are discussed.